Historical development of marketing and its implications to the future of marketing discipline - Chesula, Osman Wechuli; Kiriinya, Stephen Ntuara; Rintari, Ann (Research Journal in Advanced Social Sciences, 2021)
This paper sought to examine the development of marketing (theory, scholarship and practice) and accounted for that evolution. It also sought to determine the implications that the developments have for the marketing theory, scholarship and practice in future. The paper is based on the empirical analysis of important literature from scholarly articles. From its findings, it is evident that marketing activities are as old as humanity and the development of marketing discipline is gradual having had less attention in early centuries. However; attention to marketing as an important function emerged in the late 19th century. It is also evident that marketing theory borrows a lot from other disciplines and it’s still not clear which topics comprehensively constitute marketing theory. The insights from the analysis bring out the contribution of marketing theory to marketing scholarship and practice. A lot is expected to change in the marketing field owing to globalization, consumer preferences, inventions and innovations in information and communication technology and importance of relationship building. Marketing research is one of the areas that are expected to see significant changes over the years as new approaches emerge.